2016
DOI: 10.2217/pgs-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in known and Novel Candidate Genes Predisposing to Statin-Associated Myopathy

Abstract: These findings support the role of rare variants and nominate loci for follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…The ancestry of the cases were determined from genotype data obtained from the HumanOmni2.5 microarray and whole exome sequencing as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancestry of the cases were determined from genotype data obtained from the HumanOmni2.5 microarray and whole exome sequencing as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Existence of selected CNVs was independently assessed either in exome sequence data that were available for each of the participants (DNA fragmentation, sequencing library preparation, library sequencing and CNV variant detection and annotation were performed as described) and/or validated and genotyped using a Universal Probe Library copy number assays using the LightCycler 480 Instrument (Roche Life Science, Prague, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to discover additional common variants related to statin-related muscle injury have failed to yield replicable findings [2022]. A recent study from the Czech Republic conducted whole-exome sequencing on 88 patients with mild statin-associated muscle toxicity, reporting an increased burden of rare variation in 24 genes [23]. We did not replicate these findings in our study, perhaps due to different phenotypes as most of our patients have more severe SRM.…”
Section: Discussionmentioning
confidence: 54%
“…40 For instance, researchers identified a heterozygote truncating mutation within CLCN1 gene by performing WES in patients with statin-associated myopathy and therefore, determined a novel candidate gene of this disease. 69 Additionally, it has been suggested that rare variants are likely to have appeared more recently than common variants, leading to reduced LD and making them more easily interpretable than common variants. 21 Moreover, early studies have indicated that rare and lowfrequency genetic variants may have larger effects on complex disease phenotypes and susceptibility than common variants.…”
Section: Benefits Of Identifying Rare and Low-frequency Variantsmentioning
confidence: 99%